Reformulasi Sanksi Pidana bagi Pelaku Eutanasia dalam Hukum Pidana Indonesia - Roli Pebrianto (Kajian Ilmiah Hukum dan Kenegaraan, 2022)
Purpose: To find out about eutanasia from the perspective of legal protection and human rights; as well as criminal law policies related to sanctions for eutanasia perpetrators in Indonesia. Research Methodology: The method used in this research is normative legal research, while the approach used is a statute approach, namely the Indonesian Criminal Code. Results: Prison sentence arrangements for doctors who practice active eutanasia need to be considered and studied further which must accommodate many things including the doctor's obligation to cure patients on the one hand, while on the other hand there is the patient's right to end his life because his illness is unlikely to be cured. Limitations: This research is limited to normative legal research that uses only primary legal materials, namely a comparison of the application of the eutanasia article in the old and new Criminal Codes, as well as threats of sanctions that are felt to have not fulfilled the value of justice. Contribution: In criminal law policies, it is necessary to consider alternative punishments other than imprisonment, for example fines. In this case, it is not necessary to remove the threat of imprisonment in Article 461 of the new Criminal Code, but to add a new article or paragraph which accommodates other forms of sanctions as an alternative to imprisonment. So that imprisonment will be imposed selectively, limitedly, and casuistically.